Analysis of Cs-137 Diffusion in Clay Soil and Kaolin from West Kalimantan with Groundwater Saturation - Kurniawan, Muhammad Haidar; Kundari, Noor Anis; Ekaningrum, Nurul Efri (Journal La Lifesci, 2025)
Electricity demand in Indonesia is increasing along with economic and population growth. The plan to build a nuclear power plant (NPP) in Kalimantan needs to be accompanied by support facilities such as disposal. Research on disposal facilities in West Kalimantan is crucial because of its proximity to the planned NPP, and using local materials like kaolin and clay will be more economical. In this study, compacted clay and kaolin layers were used as part of the engineered barrier at the disposal site. The goal is to prevent the release of Cs-137 from the facility into the unsaturated zone. XRD, XRF, and ICP-OES were used to characterize the clay and kaolin studied. Analysis revealed many absorbent minerals suitable for the engineered barrier at the disposal site.To evaluate the diffusion coefficient (Da) of Cs-137 in compacted clay and kaolin samples, a vertical diffusion model was employed. The diffusion coefficient was measured in a diffusion column unit with varying times and densities. Fick's law equation was used to calculate the Da value for the samples. The results showed that the diffusion coefficient for kaolin ranged from 2.75 x 10-12 to 3.96 x 10-12 m²/s, and for clay from 1.62 x 10-12 to 2.92 x 10-12 m²/s. In clay and kaolin samples, density affected the diffusion rate; higher density resulted in a lower Da value. However, time did not impact the Da value. The diffusion coefficient in kaolin was twice as fast as in clay samples.In the safety assessment experiment with RESRAD Offsite, a 0.2 m kaolin layer was sufficient.